2018
DOI: 10.1016/j.contraception.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after elective sterilization procedures — a comparative retrospective cohort study of Medicaid patients

Abstract: This propensity score matching analysis confirms that pelvic pain and AUB are common in women before and after sterilization regardless of whether the procedure is performed hysteroscopically or laparoscopically. Moreover, HS is associated with a significantly lower risk of hysterectomy or a CPP diagnosis in the 24months poststerilization when compared to TL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Based on our inclusion/exclusion criteria, through full-text screening, we identified 61 studies for inclusion. 1 , 3 , 6 – 8 , 11 , 13 – 15 , 21 , 22 , 24 31 , 34 41 , 44 46 , 49 61 , 63 67 , 69 – 73 , 75 , 78 80 , 82 84 , 87 We included no additional studies through reference search and 4 additional studies solicited from coauthors that were not otherwise included, 19 , 23 , 43 , 81 resulting in a total sample of 65 studies, all of which were published in the English language; hence, no studies were excluded based on language.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our inclusion/exclusion criteria, through full-text screening, we identified 61 studies for inclusion. 1 , 3 , 6 – 8 , 11 , 13 – 15 , 21 , 22 , 24 31 , 34 41 , 44 46 , 49 61 , 63 67 , 69 – 73 , 75 , 78 80 , 82 84 , 87 We included no additional studies through reference search and 4 additional studies solicited from coauthors that were not otherwise included, 19 , 23 , 43 , 81 resulting in a total sample of 65 studies, all of which were published in the English language; hence, no studies were excluded based on language.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics and results of all included studies can be found in Table 1. Of the studies included for the narrative synthesis, six compared effectiveness; [24][25][26][27][28][29] sixteen assessed adverse effects; 11,24,25,[28][29][30][31][32][33][34][35][36][37][38][39][40] three compared patient recovery; 25,35,36 ve compared non-contraceptive bene ts, primarily the reduction of cancer risk; 34, 41-44 six compared tolerability; 24,25,[27][28][29]44 four compared costs to the healthcare system; 28,[45][46][47] and six compared length of procedures. 11,28,35,36,40,47 No included studies compared accessibility, eligibility, or follow-up required.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sixteen studies assessed adverse effects using prospective/retrospective cohort designs. Results are organized by intervention: six compared hysteroscopic tubal occlusion and laparoscopic tubal ligation, 24,25,[28][29][30][31] three compared laparoscopic tubal ligation and a control, [32][33][34] ve compared laparoscopic tubal ligation and bilateral salpingectomy, 11,[35][36][37]40 one compared hysteroscopic tubal occlusion, laparoscopic tubal ligation with controls, and bilateral salpingectomy with controls, 38 and one compared bilateral salpingectomy with laparoscopic tubal ligation and with matched controls. 39 Hysteroscopic tubal occlusion vs. Laparoscopic tubal ligationTwo studies 24,30 found no statistically signi cant difference in rates of adverse effects including abnormal uterine bleeding, pelvic pain, or opioid managed pain between the two interventions.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 2 more Smart Citations